ASSA14-03-06 Activation of D4 dopamine receptor decreases AT1 angiotensin II receptor expression in rat renal proximal tubule cells. (1st December 2014) - Chen, K; Deng, K; Wang, X; Wang, Z; Zheng, S; Ren, H; He, D; Han, Y; Asico, LD; Jose, PA; Zeng, C
Abstract : Objective: The dopaminergic and renin angiotensin systems interact to regulate blood pressure. Disruption of the D4 dopamine receptor gene in mice produces hypertension that is associated with increased renal AT1 receptor expression. We hypothesise that the D4 receptor can inhibit AT1 receptor expression and function in renal proximal tubules (RPTs) cells from Wistar-Kyoto (WKY) rats but the D4 receptor regulation of AT1 receptor is aberrant in RPT cells from spontaneously hypertensive rats (SHRs). Methods: Immortalised RPT cells from WKY and SHRs were treated by The D4 receptor agonist, PD168077 to determine the AT1 receptor protein expression and Na + -K + ATPase activity, and treated by calcium channel blocker, nicardipine to determine the signalling molecule. Rats were treated in vivo by D4 receptor agonist and losartan to obverse the anti-hypertensive and natriuretic effect. Results: The D4 receptor agonist, PD168077, decreased AT1 receptor protein expression in a time (0–30 hrs)- and concentration (10 –9 –10 –5 M)-dependent manner in WKY RPT cells. By contrast, in SHR cells, PD168077 (10 –6 M) increased AT1 receptor protein expression. The inhibitory effect of D4 receptor on AT1 receptor expression in WKY RPT cells was blocked by a calcium channel blocker, nicardipine (10 –6 M), or calcium-free medium, indicating that calcium is involved as a signalling molecule in the D4 receptor-mediated signalling pathway. Angiotensin II (10 –11 M) increased Na + -K + ATPase activity in WKY cells. Pretreatment with PD168077 (10 –6 M/24hrs) decreased the stimulatory effect of angiotensin II on Na + -K + ATPase activity in WKY cells. However, in SHR cells, the inhibitory effect of D4 receptor on angiotensin II-mediated stimulation of Na + -K + ATPase activity was aberrant; pretreatment with D4 receptor agonist augmented the stimulatory effect of AT1 receptor on Na + -K + ATPase activity in SHR cells. This was confirmed in in vivo studies; pre-treatment with PD128077 for one week augmented the anti-hypertensive and natriuretic effect of losartan in SHRs but not in WKY rats. Conclusions: We suggest that an aberrant interaction between D4 and AT1 receptors may play a role in the abnormal regulation of sodium excretion and blood pressure in hypertension.